Artistic individuality of Fariza Ongarsynova - Kamarova Н.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The article analyzes poetry of Fariza Ongarsynova, who became a maitre of Kazakh poetry. Fariza’s poems introduce us with a national idea and national thinking of Kazakh people. Fariza Ongarsynova’s poetry considers poems written on the theme of Mangistau region and praising the harmony of a man and nature to promote the national idea of Kazakh people The article considers poems dedicated to the topic of Dala, Kyr, etc. The article contents an objective assessment of the poetry. It reveals an use of landscapes, steppe images in the poet’s work. One of the ways of expressing her poetic nature is through exploring the poet’s distinctive personality. Thanks to the study of the characteristic poetic feature of Fariza Ongarsynova, it is possible to define her poetic mastery. The article focuses on artistic individuality, ideological and thematic themes of poetry, contribution to the national artistic tradition, a place and figurative character in modern Kazakh poetry.